filmov
tv
Prove that A minus (B intersection C) = (A - B) U (A U C) and A-(B U C )= (A-B) intersection (A-C).
![preview_player](https://i.ytimg.com/vi/IfyGyXLl14g/maxresdefault.jpg)
Показать описание
Prove that A minus (B union C) is equal to (A minus B ) Intersection (A minus C).
Prove that A minus (B union C)=(A minus B) union (A minus C).
Prove that A-(B U C)= (A-B) intersection (A-C).
Prove that A-(B intersection C)=(A-B) union (A-C).
Theorem: For any three sets A,B and C the following laws known as De Morgan's laws (in the form) hold.
(1) A - (B U C) = (A - B) intersection (A - C)
(2) A - (B intersection C) = (A - B) U (A - C).
De Morgan's laws || Class 11 || Sets || Maths Analysis
De Morgan's laws Explanation in Hindi.
#Sets #DeMorganslaws #MathsAnalysis #CBSEClass11
Prove that A minus (B union C)=(A minus B) union (A minus C).
Prove that A-(B U C)= (A-B) intersection (A-C).
Prove that A-(B intersection C)=(A-B) union (A-C).
Theorem: For any three sets A,B and C the following laws known as De Morgan's laws (in the form) hold.
(1) A - (B U C) = (A - B) intersection (A - C)
(2) A - (B intersection C) = (A - B) U (A - C).
De Morgan's laws || Class 11 || Sets || Maths Analysis
De Morgan's laws Explanation in Hindi.
#Sets #DeMorganslaws #MathsAnalysis #CBSEClass11